Associations between intimate partner violence and adverse birth outcomes during pregnancy: a systematic review and meta-analysis - Guo, Cancan; Wan, Mengtong; Wang, Yue; Wang, Peijie; Tousey-Pfarrer, Marissa; Liu, Haoyang; Yu, Liangming; Jian, Lingqi; Zhang, Mengting; Yang, Ziqi; Ge, Fenfen; Zhang, Jun (Frontiers in Medicine, 2023)
Background: Intimate partner violence (IPV) has been associated with elevated risk of multiple adverse birth outcomes, yet little is known about how specific-IPV influence adverse birth outcomes. The aim of this study is to examine the association between IPV during pregnancy and adverse birth outcomes (i.e., preterm birth, low birth weight and stillbirth). Methods:¬ Systematic searches were conducted using four databases: EMBASE, Web of Science, PubMed and CINAHL for observational studies published from January 1, 2011 to August 31, 2021. Two reviewers independently carried out the literature search, study selection, data extraction, assessment of study, and risk of bias assessment; disagreements were resolved by a third reviewer. A random effect model was used to calculate the odds ratio (OR) with 95% confidence interval (CI) for preterm birth, low birth weight and stillbirth. I2 statistic accompanied by chi-square p-value were used to assess heterogeneity, and funnel plot and Peter’s test were uesd to assess publication bias. Results: 23 studies met the inclusion criterion. IPV was associated with preterm birth (OR=1.84, 95% CI 1.37 - 2.49; I2 = 88%), low birth weight (OR=2.73, 95% CI 1.66 - 4.48; I2 = 95%) and stillbirth (OR=1.74, 95% CI 0.86 - 3.54; I2 = 64%). We attained comparable results among all specific-IPV including physical, sexual, emotional, and mixed. Conclusions: IPV and specific IPV during pregnancy was significantly associated with adverse birth outcomes, especially for physical IPV. An urgent need for greater action to prevent or intervene IPV during pregnancy is warranted.